Serinocarbapenemasas de clase A en enterobacterias - De la Lastra J., Virginia; Ulloa F., M. Teresa; Pinto C., M. Eugenia; Vidal C., Mario; Silva O., Francisco (Revista Hospital Clínico Universidad de Chile, 2010)
Bacterial resistance to B-lactam antibiotics is becoming a matter of great concern. The rapid emergence of extended spectrum B-lactamases (ESBLs) in Enterobacteriaceae has made the carbapenems the drugs of choice to treat severe infections due to these bacteria. The emergence and spread of carbapenem-resistant enterobacteria restricts the antibiotic therapy. ESBLs or AmpC enzyme hiperproduction in combination with porin loss are regarded as the main mechanisms of carbapenem resistance in Enterobacteriaceae. Recently, it has been described the emergence of serine-carbapenemases (Class A carbapenemases). In ourcountry carbapenemases has been reported only in non-fermentative Gram-negative bacilli. There are still no reports of enterobacteria with these enzymes, but their rapid spread makes surveillance a mayor priority. Therefore tests able to detect the first carbapenemase producing enterobacteria are needed. It has been proposed to use the modified Hodge Test, but this testhas too many false positive results in areas with high prevalence of ESBLs, wich is the reality of our country. Boronic acid (BA) compounds were recently reported to be reversible inhibitors of KPC serinecarbapenemases. Tests using BA has been used with success for the accurate identification of KPC carbapenemases. With this threat, to watch the local epidemiology hasbecome a matter of great importance.